Augmented reality mobile application for human blood circulatory system - Tey, Chwee Teng (2014)
Learning the topic of human blood circulatory system in form three science syllabus using conventional way was inadequate for the students to imagine and understand the whole circulatory process in a short time. Students get bored when they were learning in traditional method by reading the text and see the picture on a book. Therefore, an Augmented Reality Mobile Application for Human Blood Circulatory System was developed to enhance the learning experience for students or anyone who wish to learn more about the human blood circulatory system with more interesting. This AR mobile application was developed by using ARToolKit applying the marker-based tracking technique with template marker. There were three main topics of the learning materials which are the heart, blood vessels and blood. Basically, this AR application is used along with the AR book where the students can aim camera of their smartphone or tab at the marker to see and interact with the related 3D models object. This AR mobile application also provides some teaching modules such as the educational videos, anatomies and the quizzes besides applying the Augmented Reality technology. Based on the survey results from the users, it is found that this AR application had an ability to increase the student understanding about the topic of the human blood circulatory system in an interesting and effective way.